2020
DOI: 10.1111/ped.14179
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid tumor surveillance using ultrasound in childhood cancer survivors

Abstract: Background: The optimal method for thyroid cancer screening in childhood cancer survivors (CCSs) who received radiation involving the thyroid gland is still debated. We describe a case series of ultrasound surveillance for thyroid tumor in CCSs in our institute. Methods: We conducted thyroid tumor surveillance for CCSs with a history of radiation therapy involving the thyroid. The basic screening method was palpation. Thyroid ultrasound was also performed for patients who agreed after its benefits and risks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Compared with the control group, the levels of the observation group were significantly higher than those of the control group. The results of the study showed that the two surgical methods both damaged parathyroid function and reduced immune function, but the modified nonpneumatic transaxillary approach significantly reduced the impact on parathyroid function and immune function [ 17 ]. The reason is that the improved nonpneumatic subaxillary approach has established the operative cavity, and the surgical field of vision is relatively larger.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the levels of the observation group were significantly higher than those of the control group. The results of the study showed that the two surgical methods both damaged parathyroid function and reduced immune function, but the modified nonpneumatic transaxillary approach significantly reduced the impact on parathyroid function and immune function [ 17 ]. The reason is that the improved nonpneumatic subaxillary approach has established the operative cavity, and the surgical field of vision is relatively larger.…”
Section: Discussionmentioning
confidence: 99%